Kajian Sifat Organoleptik Dan Masa Simpan Tempe Kedelai Dengan Beberapa Jenis Kemasan - Supriadi Umami; I Ketut Swirya Jaya; Made Darawati; I Gde Narda Widiada (Poltekkes Kemenkes Mataram, 2018)
Background. Tempe soybeans are one of the traditional foods that have long been known in Indonesia. Tempe fermentation process will change soybeans into tempeh which has a better aroma, taste, texture, nutritional value and digestibility. The taste of tempe is determined by the type of soybeans and the type of packaging during fermentation and the storability of soybean tempeh. Research Methods. This study used an experimental method with experimental design using a completely randomized design (CRD). Research Result. The results of organoleptic properties in this study with the best color, aroma and texture parameters with t1 treatment were using plastic packaging and the best taste parameters, namely with t3 treatment using teak leaf packaging. The observation of the storage capacity of soybean tempeh for two days of storage at 300C with various types of packaging with evaluation parameters including the color, aroma, taste and texture of the best soybean tempe was the storage capacity of soybean tempe in treatment t1 using plastic packaging. Conclusion. The best organoleptic properties with color, aroma and taste parameters with treatment t1 (plastic packaging) for taste parameters at the best treatment level are t3 (teak leaf packaging) and shelf life of soybean tempeh based on organoleptic properties with the best parameters of color, aroma, taste, and texture soybean tempe with treatment level t1 (plastic packaging).